INFLUENCE OF DRAMA STAGING BAN "MASTODON DAN BURUNG KONDOR" IN RENDRA’S SYMBOLIC CAPITAL FULFILLMENT - Neisya - (HOLISTICS, 2016)
Language is a tool for a person to represent and express themselves to others. Lacan (2008) believes that human subjects cannot exist without language, but the subject cannot be reduced to language. This power of language is used by WS Rendra. Through language, Rendra is able to express his ideology and views on social world chaos around him. The purposes of this article are to reveal the habitus which influence Rendra in making Mastodon dan Burung Kondor as well as the capital getting by Rendra on the ban of play performance and the effect of it toward his career trajectory in Indonesian literature arena. The method used in this study is library research and analytical descriptive. From the analyses, it can be summarized that Rendra's dissident mental and the events in 1970 become habitus in making Mastodon dan Burung Kondor. Meanwhile, the capital obtained by Rendra is symbolic capital.